Pengaruh Perputaran Piutang, Pertumbuhan Penjualan dan Current Rasio Terhadap Profitabilitas - Thomas Firdaus Hutahaean; Winda Adelina (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
In order to obtain maximum profit, a company is expected to consider important elements in the company. The important elements are receivable turnover, sales growth, current ratio and profitability. Therefore, the objective of the study is to examine the effect of receivable turnover, sales growth and current ratio on profitability in the listed companies in the Indonesia Stock Exchange food and beverage subsector in 2011-2015. This is a descriptive study with a quantitative approach. The research populations were all food and beverage subsector companies. The research samples were drawn by using purposive sampling technique consisting of 14 companies. The data collection was performed by library research and documentation techniques via the internet with the site www.idx.co.id while the research data were analyzed by using multiple linear regression analysis. The result of the study on the hypothesis showed that simultaneous, accounts receivable turnover, sales growth and current ratio had a positive and significant effect on profitability. The hypothesis testing partially showed that accounts receivable turnover did not have positive influence and significant effect on profitability, sales growth did not have a negative and not significant effect on profitability, while current ratin had a positive and significant effect on profitability. The value of the determination coefficient on the hypothesis is 0.205% showing that profitability can be explained by accounts receivable turnover, sales growth and current ratio up to 20.5%, while the remaining 79.5% were affected by other variables discussed in this study.